2018
DOI: 10.3892/ijmm.2018.4025
|View full text |Cite
|
Sign up to set email alerts
|

Crude protein from spirulina increases the viability of CCD‑986sk cells via the EGFR/MAPK signaling pathway

Abstract: Spirulina, an edible blue-green alga, has great potential for various applications in human health, possibly including reduced skin aging. The mechanisms by which spirulina crude protein (SPCP) may influence human skin fibroblast viability are not yet understood; therefore, a human dermal fibroblast cell line (CCD-986sk) was used as a cell model system to study the influence of SPCP on human skin fibroblast viability. An enzyme-linked immunosorbent assay showed that collagen formation improved in SPCP-treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 46 publications
1
13
0
1
Order By: Relevance
“…It has been reported that only phosphorylated ERK1/2 is active (42). In a previous study, it was demonstrated that SPcP increased the phosphorylation level of ERK1/2 (27). Thus, the phosphorylation level of ERK1/2 in the granulation tissue of c57BL/6 mice was determined in the present study.…”
Section: Discussionmentioning
confidence: 54%
See 4 more Smart Citations
“…It has been reported that only phosphorylated ERK1/2 is active (42). In a previous study, it was demonstrated that SPcP increased the phosphorylation level of ERK1/2 (27). Thus, the phosphorylation level of ERK1/2 in the granulation tissue of c57BL/6 mice was determined in the present study.…”
Section: Discussionmentioning
confidence: 54%
“…In particular, type I collagen is the most prevalent of the fibril-forming collagens (48). According to previous studies, it has been found that SPcP promotes the secretion of collagen in ccd-986sk cells (27). In the present study, the expression level of type I collagen was determined in granulation tissue of c57BL/6 mice.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations